Hyaluronic acid modified chuanxiong oil liposomes as a novel therapeutic agent for photoaging prevention - Xiaofang He; Yue Hu; Yuanyuan Wu; Yuting Luo; Huiyi Feng; Qianqian Wu; Haolin Liu; Leying Gao; Haofeng Yang; Yu Long; Yin Ma; Xiaoqiu Li; et al. (Scientific Reports)
Abstract The gradual increase in ultraviolet B (UVB) health hazards to human skin, coupled with the irritation associated with existing sunscreen products, underscores the critical need for the development of natural sunscreens to combat UVB-induced photoaging. Chuanxiong oil (CXO) and hyaluronic acid (HA) possess excellent antioxidant and anti-apoptotic properties, which are closely linked to the mechanisms of photoaging. In this study, a composite nano-system (HA-CXO-Lip) comprising chuanxiong oil (CXO) and hyaluronic acid (HA) was initially fabricated. Subsequently, both in vitro HaCaT cell models and in vivo murine photoaging models were established to systematically evaluate the therapeutic efficacy and mechanistic actions of HA-CXO-Lip against photoaging under controlled experimental conditions. The investigation encompassed comprehensive assessments of its pharmacological effects and underlying molecular mechanisms through multimodal experimental approaches. Vitro experiments showed HA-CXO-Lip significantly reduced intracellular reactive oxygen species (ROS) levels and senescence-associated β-galactosidase (SA-β-Gal) activity. Furthermore, HA-CXO-Lip restored the levels of antioxidant enzymes, including superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and hydroxyproline (HYP), while also decreasing the levels of lipid metabolites such as 4-hydroxynonenal (4-HNE) and malondialdehyde (MDA). These findings indicate that HA-CXO-Lip effectively inhibits excessive oxidative stress. Additionally, HA-CXO-Lip inhibited apoptosis by reducing Bax levels and enhancing Bcl-2 expression in HaCaT cells. In vivo studies demonstrated that HA-CXO-Lip significantly reduced UVB irradiation-induced erythema and epidermal thickening in the backs of mice. It restored the orderly arrangement of collagen fibers and inhibited the activation of the core senescence pathway, AKT/mTOR, along with the downstream expression of matrix metalloproteinase 9 (MMP9), resulting in a decrease in collagen I disassembly. Additionally, HA-CXO-Lip was shown to significantly decrease the number of apoptotic cells, as indicated by the expression of the apoptosis marker cleaved cysteine aspartic protease-3 (C-Caspase-3) and the surface type I transmembrane glycoprotein (CD44), thereby further inhibiting apoptosis. The findings of this study suggest that HA-CXO-Lip can exert anti-photoaging effects through its antioxidant and anti-apoptotic properties, highlighting the synergistic efficacy of CXO and HA, which holds promise for the prevention and treatment of photoaging.